다문화 학교환경이 청소년의 다문화태도에 미치는 영향 - 아영아; Young Ah Ah (청소년복지연구, 2013)
본 연구는 청소년들이 다문화사회에 적응하기 위한 기초자료를 확보하기 위해 일반청소년을 대상으로 이들의 다문화에 대한 태도 및 다문화 학교환경에 대한 인식수준을 살펴보고 다문화 태도에 영향을 미치는 다문화 학교환경요인을 탐색하고자 설계되었다. 자료 수집은 2012년 5월 현재 다문화가정 학생이 재학 중인 부산시내 소재한 초·중·고등학교 학생을 대상으로 설문지를 통해 자료수집이 이루어졌으며, 876부의 설문지가 최종분석에 사용되었다. 연구결과 조사대상자의 다문화태도는 보통 이상으로 긍정적인 수준으로 나타났으며, 다문화 학교환경에 대한 인식수준 역시 보통 이상으로 긍정적인 것으로 나타났다. 다문화 학교환경이 청소년의 다문화 태도에 미치는 영향에서는 우선, 다문화 신뢰수용성에서는 상호협력, 동등지위, 친밀한 교류가 유의한 영향을 주는 변수로 나타났으며, 다문화 편견과 다문화의 부정적 영향력에서는 동등한 지위 변수만이 유의한 영향력을 미치는 변수로 나타났다. 다문화태도 전체에서는 동등한 지위와 친밀한 교류 등의 변수가 유의한 영향력을 미치는 변수로 나타났다. 이러한 결과를 토대로 학교현장에서의 다문화태도 정립을 위한 통합적 접근이 필요함을 제언하였다. This study is designed to examine general adolescents` attitudes towards multiple cultures and recognition level on multicultural school environments, and explore the multicultural school environmental factors which influence the multicultural attitudes, in order to collect basic materials to adapt to a multicultural society. The data collection was conducted through questionnaires for students from elementary, middle and high schools located in Busan, in which students from multicultural families attended as of May 2012; total 876 copies of the questionnaires were used in the final analysis. In the result, the multicultural attitudes of the research subjects were found to be more positive than average, and their recognition levels on multicultural school environment were also positive on above average. Regarding the effects of multicultural school environment on the multicultural attitudes of adolescents, first, mutual cooperation, equal status and intimate exchange were shown to be the variables which gave significant influences in trust receptivity of multiple cultures; in the multicultural bias and negative influence of multiple cultures, only equal status was the factor that influenced significantly. In the whole multicultural attitudes, it was demonstrated that factors such as the equal status and the intimate exchange were the variables that had significant influence. Based on the results, the study suggested the necessity of integral access to establish the multicultural attitudes in the school environment.